Isolation of streptococcus tigurinus - a novel member of streptococcus mitis group from a case of periodontitis - Dhotre, Shree V.; Mehetre, Gajanan T.; Dharne, Mahesh S.; Suryawanshi, Namdev M.; Nagoba, Basavraj S. (FEMS Microbiology Letters, 2014)
Streptococcus tigurinus is a new member of the Streptococcus viridians group and is closely related to Streptococcus mitis, Streptococcus pneumoniae, Streptococcus pseudopneumoniae, Streptococcus oralis, and Streptococcus infantis. The type strain AZ_3a(T) of S. tigurinus was originally isolated from a patient with infective endocarditis. Accurate identification of S. tigurinus is facilitated only by newer molecular methods like 16S rRNA gene analysis. During the course of study on bacteraemia and infective endocarditis with reference to periodontitis and viridians group of streptococci, a strain of S. tigurinus isolated from subgingival plaque of a patient with periodontitis identified by 16S rRNA gene analysis, which was originally identified as Streptococcus pluranimalium by Vitek 2. Confirmation by 16S rRNA gene analysis showed 99.39% similarity (1476/1485 bp) with S. tigurinus AZ_3a(T) (AORU01000002). To the best of our knowledge, this is the first report of isolation of S. tigurinus from the oral cavity of a periodontitis patient.
Keywords: periodontitis; Streptococcus tigurinus; VGS

Complete metagenome sequencing based bacterial diversity and functional insights from basaltic hot spring of Unkeshwar, Maharashtra, India - Mehetre, Gajanan T.; Paranjpe, Aditi S.; Dastager, Syed Gulam; Dharne, Mahesh S. (Genomics Data, 2016)
Unkeshwar hot springs are located at geographical South East Deccan Continental basalt of India. Here, we report the microbial community analysis of this hot spring using whole metagenome shotgun sequencing approach. The analysis revealed a total of 848,096 reads with 212.87Mbps with 50.87% G+C content. Metagenomic sequences were deposited in SRA database with accession number (SUB1242219). Community analysis revealed 99.98% sequences belonging to bacteria and 0.01% to archaea and 0.01% to Viruses. The data obtained revealed 41 phyla including bacteria and Archaea and including 719 different species. In taxonomic analysis, the dominant phyla were found as, Actinobacteria (56%), Verrucomicrobia (24%), Bacteriodes (13%), Deinococcus-Thermus (3%) and firmicutes (2%) and Viruses (2%). Furthermore, functional annotation using pathway information revealed dynamic potential of hot spring community in terms of metabolism, environmental information processing, cellular processes and other important aspects. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis of each contig sequence by assigning KEGG Orthology (KO) numbers revealed contig sequences that were assigned to metabolism, organismal system, Environmental Information Processing, cellular processes and human diseases with some unclassified sequences. The Unkeshwar hot springs offer rich phylogenetic diversity and metabolic potential for biotechnological applications.

Detection of clostridium tetani in human clinical samples using tetX specific primers targeting the neurotoxin - Ganesh, Madhu; Sheikh, Nasira K.; Shah, Pooja; Mehetre, Gajanan T.; Dharne, Mahesh S.; Nagoba, Basavraj S. (Journal of Infection and Public Health, 2016)
Tetanus resulting from ear injury remains an important health problem, particularly in the developing world. We report the successful detection of Clostridium tetani using tetX specific primers targeting the Cl. tetani neurotoxin. The sample was obtained from an ear discharge of a case of otogenic tetanus in a 2-year-old male child. Based on the culture results of the ear discharge, Gram staining and virulence testing by genotyping, a diagnosis of tetanus was confirmed. This is the first report from India on the successful detection of Cl. tetani in a human clinical sample using tetX specific primers targeting the Cl. tetani neurotoxin. (C) 2015 King Saud Bin Abdulaziz University for Health Sciences. Published by Elsevier Limited. All rights reserved.
Keywords: Cl. tetani; Neurotoxin; Otogenic tetanus; Trismus

Investigation of microbial diversity in geothermal hot springs in Unkeshwar, India, based on 16S rRNA amplicon metagenome sequencing - Mehetre, Gajanan T.; Paranjpe, Aditi; Dastager, Syed Gulam; Dharne, Mahesh S. (Genome Announcements, 2016)
Microbial diversity in geothermal waters of the Unkeshwar hot springs in Maharashtra, India, was studied using 16S rRNA amplicon metagenomic sequencing. Taxonomic analysis revealed the presence of Bacteroidetes , Proteobacteria , Cyanobacteria , Actinobacteria , Archeae , and OD1 phyla. Metabolic function prediction analysis indicated a battery of biological information systems indicating rich and novel microbial diversity, with potential biotechnological applications in this niche.

Untapped bacterial diversity and metabolic potential within Unkeshwar hot springs, India - Mehetre, Gajanan T. (Archives of Microbiology, 2018)
Hot springs support diverse and interesting groups of microorganisms adapted to extreme conditions and gaining attention in biotechnological applications. However, due to limitations of cultivation methods, a majority of such extremophiles remain uncultivated and unexplored. The advent of multiple cultivation conditions and specialized culture media could possibly aid to access the unexplored microbial portion of hot springs. In the present study, different media and isolation strategies were applied to isolate hitherto unexplored bacterial taxa in the water samples collected from Unkeshwar hot springs, India. Molecular, phylogenetic and predictive functional characterization of the isolated bacterial population was done using 16S rRNA sequencing coupled with Tax4Fun tools. Furthermore, representative isolates were screened for important enzymes (cellulase, xylanase, amylase, and protease) and heavy metal tolerance (chromium, arsenic) properties. A total of 454 bacterial isolates obtained were mapped into 57 unique bacterial genera and 4 different bacterial phyla. Interestingly, 37 genera not previously isolated from Indian hot springs, were isolated for the first time in the present study. However, most of these genera (23 out of 37) were reported only in metagenomics studies from Indian and global hot springs. Furthermore, around 14 genera not previously cultivated and not detected in metagenomics studies of hot springs are documented here. The metabolic potential was ascertained by determining the abundance of specific genes using in silico based Tax4Fun tool, which identified around 315 metabolic pathways for metabolism of carbohydrates, synthesis of secondary metabolites and degradation of xenobiotic compounds. Bioprospection study revealed that 33 and 25 bacterial genera were positive for enzyme production and resistance to the heavy metals, respectively. The present study revealed the advantages of cultivation methods using a comprehensive multiple isolation approach for exploring untapped and unique bacterial diversity, and also utilities for various biotechnological and environmental applications.
Keywords: Bacterial diversity; Bioprospecting; Cultivation; Heavy metals; Untapped

Bioactivities and molecular networking-based elucidation of metabolites of potent actinobacterial strains isolated from the Unkeshwar geothermal springs in India - Mehetre, Gajanan T.; Vinodh, J. S.; Burkul, Bhushan B.; Desai, D.; Santhakumari, B.; Dharne, Mahesh S.; Dastager, Syed G (RSC Advances, 2019)
The bioactive potential of Actinobacteria endemic to hot springs has rarely been investigated. This study highlights the cultivable diversity and bioactivities of Actinobacteria associated with the Unkeshwar hot springs, India. Potent strains were evaluated for their biosynthetic potentials and metabolite analysis was performed using effective dereplication molecular networking tools. A total of 86 actinobacterial strains were isolated and grouped into 21 distinct genera, based on 16S rRNA gene sequence analysis. These strains included rare members such as Micromonospora, Marmoricola, Actinomadura, Cellulomonas, Cellulosimicrobium, Janibacter, Rothia, Barrentisimonas, Dietzia and Glycomyces. In antimicrobial screening, Micromonospora sp. strain GH99 and Streptomyces sp. strain GH176 were found to be potent antimicrobial strains. The metabolic extracts of these strains exhibited strong antimicrobial activity against Staphylococcus epidermidis (NCIM 2493), Shigella flexneri (NCIM 5265), Klebsiella pneumonia (NCIM 2098), and Salmonella abony (NCIM 2257). The extracts also displayed strong anti-biofilm and anticancer activities against Pseudomonas aeruginosa (NCIM 5029), Acinetobacter junii (NCIM 5188) and breast cancer cell line MCF7, respectively. Both strains also tested positive for the presence of the PKS biosynthetic gene cluster in their genomes. To effectively delineate the secondary metabolites, the extracts were subjected to MS/MS-guided molecular networking analysis. Structurally diverse compounds including the polyketides 22-dehydroxymethyl-kijanolide (GH99 strain) and Abyssomicin I (GH176 strain) were detected in the extracts. Interestingly, Brevianamide F was detected in the extract of Micromonospora, which has previously been mostly found in fungal species. Other compounds such as cyclic tripeptides, Cyclo(l-Pro-d-Ile) and Cyclo(d-Pro-l-Phe), were also identified in this strain. In summary, for the first time, we explored the diversity of Actinobacteria and evaluated their bioactive potential from the Unkeshwar hot springs. The potent strains isolated in the study could be useful in drug discovery programs.

Biodegradation of mixed polycyclic aromatic hydrocarbons by pure and mixed cultures of biosurfactant producing thermophilic and thermo-tolerant bacteria - Mehetre, Gajanan T.; Dastager, Syed G.; Dharne, Mahesh S. (Science of the Total Environment, 2019)
Applicability of thermophilic and thereto-tolerant microorganisms for biodegradation of polycyclic aromatic hydrocarbons (PAHs) with low water solubility is an interesting strategy for improving the biodegradation efficiency. In this study, we evaluated utility of thermophilic and thermo-tolerant bacteria isolated from Unkeshwar hot spring (India) for biodegradation of four different PAHs. Water samples were enriched in mineral salt medium (MSM) containing a mixture of four PAHs compounds (anthracene: ANT, fluorene: FLU, phenanthrenc: PHE and pyrene: PYR) at 37 degrees C and 50 degrees C. After growth based screening, four potent strains obtained which were identified as Aeribacillus pallidus (UCPS2), Bacillus axarquiensis (UCPD1), Bacillus siamensis (GHP76) and Bacillus subtilis subsp. inaquosorum (U277) based on the 16S rRNA gene sequence analysis. Degradation of mixed PAH compounds was evaluated by pure as well as mixed cultures under shake flask conditions using MSM supplemented with 200 mg/L concentration of PAHs (50 mg/L of each compound) for 15 days at 37 degrees C and 50 degrees C. A relatively higher degradation of ANT (92% - 96%), FLU (83% - 86%), PHE (16% - 54%) and PYR (51% - 71%) was achieved at 50 degrees C by Aeribacillus sp. (UCPS2) and mixed culture. Furthermore, crude oil was used as a substrate to study the degradation of same PAHs using these organisms which also revealed with similar results with the higher degradation at 50 degrees C. Interestingly, PAH-degrading strains were also positive for biosurfactant production. Biosurfactants were identified as the variants of surfactins (lipopeptide biosurfactants) based on analytical tools and phylogenetic analysis of the surfactin genes. Overall, this study has shown that hot spring microbes may have a potential for PAHs degradation and also biosurfactant production at a higher temperature, which could provide a novel perspective for removal of PAHs residues from oil contaminated sites. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Biodegradation; Biosurfactants; Crude oil; Mixed culture; PAHs; Thermophiles